2023
DOI: 10.37034/infeb.v5i2.563
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Tax Avoidance, Leverage dan Persediaan terhadap Audit Report Lag dengan Ukuran Perusahaan sebagai Variabel Moderating

Abstract: The purpose of this study was to examine the effect of Tax Avoidance, Leverage and Inventory on Audit Report Lag with Firm Size as a moderating variable. The information presented in this scientific paper consists of all pharmaceutical companies listed on the Indonesia Stock Exchange (IDX) in 2017-2021 in the form of 12 companies and reduced after testing several criteria to 10 companies and a total of 50 companies studied according to the research criteria. The results of this study are: tax avoidance does no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 18 publications
0
2
0
1
Order By: Relevance
“…Previous research on the relationship between tax avoidance, tax compliance, and auditor reputation on firm value has yielded different results. The impact of tax avoidance on firm value in the research of Assidi et al (2016), Siew Yee et al (2018, Septiani et al (2019); and Ilmiani & Sutrisno (2014) showed negative results between the two variables. The research of Lestari & Wardhani (2015), Anggoro & Septiani (2015), Appolos et al (2016) showed positive results between the two variables.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…Previous research on the relationship between tax avoidance, tax compliance, and auditor reputation on firm value has yielded different results. The impact of tax avoidance on firm value in the research of Assidi et al (2016), Siew Yee et al (2018, Septiani et al (2019); and Ilmiani & Sutrisno (2014) showed negative results between the two variables. The research of Lestari & Wardhani (2015), Anggoro & Septiani (2015), Appolos et al (2016) showed positive results between the two variables.…”
Section: Introductionmentioning
confidence: 91%
“…Tax avoidance behavior causes agency conflicts between companies and investors in the form of differences in interests that include the desire of the principal (investor) to conduct tax avoidance to increase the value of the firm in order to get high investment returns, while the agent (management) conducts tax avoidance so that the profitability obtained can be used to improve firm performance (Apsari & Setiawan, 2018). This is also written in the research of Ilmiani & Sutrisno (2014) where tax avoidance negatively affects the value of the firm because the higher the tax avoidance, the lower the value of the firm in the eyes of investors. H1: Tax avoidance negatively affects firm value…”
Section: The Impact Of Tax Avoidance On Firm Valuementioning
confidence: 99%
“…Keputusan manajemen memilih prinsip konservatisme disebabkan beberapa faktor, salah satunya kondisi tingkat leverage yang dimiliki perusahaan. Tingginya leverage menunjukkan utang perusahaan mendominasi anggaran operasional perusahaan (Hermanto & Nurriyah, 2023). Prinsip kehatian-hatian akan dipilih manajemen dalam memperoleh keuntungannya apabila perusahaan mengalami leverage tinggi, sebab kreditur mempunyai kewenangan untuk mengawasi arah jalannya perusahaan (Yusnaini et al, 2019).…”
Section: Pendahuluanunclassified